British Attitude towards American expansion in Caribbean - عبدالله حميد العتابي (College of Education for Women, 2019)
This paper deals with the nations of British American Struggle in Caribbean. It explains British Navy attitude of American expansion in Caribbean. Then continuation of American expansion in the same place and Britain failure to limit it. This paper high lights the beginning of acceptance between Britain's and United state, especially after British submission to United States in Caribbean. Then we study the Anglo - American harmony and the affection on the Anglo - American relation. This paper concludes that American influences in Americans which is a truth.